Lipomatous metaplasia prolongs repolarization and increases repolarization dispersion within post-infarct ventricular tachycardia circuit cites. Issue 2 (15th December 2022) - Xu, Lingyu; Zahid, Sohail; Khoshknab, Mirmilad; Moss, Juwann; Berger, Ronald D; Chrispin, Jonathan; Callans, David; Marchlinski, Francis E; Zimmerman, Stefan L; Han, Yuchi; Desjardins, Benoit; Trayanova, Natalia; et al.
Abstract: Aims: Post-infarct myocardium contains viable corridors traversing scar or lipomatous metaplasia (LM). Ventricular tachycardia (VT) circuitry has been separately reported to associate with corridors that traverse LM and with repolarization heterogeneity. We examined the association of corridor activation recovery interval (ARI) and ARI dispersion with surrounding tissue type. Methods and results: The cohort included 33 post-infarct patients from the prospective Intra-Myocardial Fat Deposition and Ventricular Tachycardia in Cardiomyopathy (INFINITY) study. We co-registered scar and corridors from late gadolinium enhanced magnetic resonance, and LM from computed tomography with intracardiac electrogram locations. Activation recovery interval was calculated during sinus or ventricular pacing, as the time interval from the minimum derivative within the QRS to the maximum derivative within the T-wave on unipolar electrograms. Regional ARI dispersion was defined as the standard deviation (SD) of ARI per AHA segment (ARISD ). Lipomatous metaplasia exhibited higher ARI than scar [325 (interquartile range 270–392) vs. 313 (255–374), P < 0.001]. Corridors critical to VT re-entry were more likely to traverse through or near LM and displayed prolonged ARI compared with non-critical corridors [355 (319–397) vs. 302 (279–333) ms, P < 0.001]. ARISD was more closely associated with LM than with scar (likelihood ratio χ 2 50 vs. 12, and 4.2-unit vs. 0.9-unit increase in 0.01*Log(ARISD ) per 1 cm 2 increase per AHA segment). Additionally, LM and scar exhibited interaction ( P < 0.001) in their association with ARISD . Conclusion: Lipomatous metaplasia is closely associated with prolonged local action potential duration of corridors and ARI dispersion, which may facilitate the propensity of VT circuit re-entry.